The central sensitization inventory: A user's manual. Issue 2 (22nd May 2018) - Neblett, Randy
Abstract : The Central Sensitization (CSI) Inventory was introduced in 2012. It was initially intended as a screener to help identify when presenting symptoms may be related to central sensitization or indicate the presence of a central sensitivity syndrome. It has now been translated and validated in a number of European, Asian, and South American languages. This article provides an overview of CSI rationale, development, recommended uses, and research results, including evidence of validity and reliability, in clinical and non‐clinical subject samples.